New planthoppers in the genus Nesomyndus (Hemiptera: Fulgoromorpha: Cixiidae) from Bismarck palms in western Madagascar, redescription of Nesomyndus australis, a key to the genus and an updated molecular phylogeny of available Oecleini - Bahder, Brian W.; Pilet, Fabian; Bartlett, Charles R.; Ratsimbazafy, Miangaly Raharimandimby; Randretsiferana, Safidinirina Armande; Razafindrakotomamonjy, Andrianatenaina; Hasinjaka, Rasolondalao Harin’hala; Labbe, Frederic; Stroiński, Adam (Zootaxa, 2025)
In a survey conducted in Northwestern Madagascar for potential vectors of palm lethal decline phytoplasmas, planthoppers belonging to the genus Nesomyndus were collected from Bismarck palms (Bismarckia nobilis). The specimens represented three species, the type species, N. australis Jacobi and two new species, here described as N. maculatus sp. nov. and N. madagascarensis sp. nov. Supplemental molecular data is provided for the cytochrome c oxidase subunit I (COI) gene (5’ and 3’ regions), histone 3 (H3) gene, 18S rRNA gene and 28S rRNA gene (D8 to D10 expansion regions) to test monophyly of Nesomyndus and its placement relative to other Oecleini.